(untitled) (Arts Faculty Journal, 2012)
As the world sails into the second decade of the new millennium, more and more people are beginning to realize the importance of folk art, their elegance and beauty. Contemporary art is a reflection of the seeds sown by folk art in different cultures hundreds of years ago. But apart from just being traditional, folk art has a significant socio-political dimension. In this paper, folk art stands as a representation of the mass public which expresses itself as popular culture. According to Ang, the populist aesthetic is based on an affirmation of the continuity of cultural forms and daily life, and on a deep- rooted desire for participation, and on emotional involvement (274). This paper will focus on the distinctive nature and role of popular folk art- the Bangladeshi Jatra and the Japanese Kabuki, which originated from the populist aesthetic of two very different cultures. Although Bangladeshi and Japanese cultures are varied, they have some common grounds on which oral or dialogue drama flourished as performance among the underprivileged masses. DOI: http://dx.doi.org/10.3329/afj.v4i0.12935 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.109-115